Shortage of Cellular ATP as a Cause of Diseases and Strategies to Enhance ATP - Johnson, Todd A.; Jinnah, H. A.; Kamatani, Naoyuki (Frontiers in Pharmacology, 2019)
Germline mutations in cellular-energy associated genes have been shown to lead to various monogenic disorders. Notably, mitochondrial disorders often impact skeletal muscle, brain, liver, heart, and kidneys, which are the body's top energy-consuming organs. However, energy-related dysfunctions have not been widely seen as causes of common diseases, although evidence points to such a link for certain disorders. During acute energy consumption, like extreme exercise, cells increase the favorability of the adenylate kinase reaction 2-ADP->ATP+AMP by AMP deaminase degrading AMP to IMP, which further degrades to inosine and then to purines hypoxanthine->xanthine->urate. Thus, increased blood urate levels may act as a barometer of extreme energy consumption. AMP deaminase deficient subjects experience some negative effects like decreased muscle power output, but also positive effects such as decreased diabetes and improved prognosis for chronic heart failure patients. That may reflect decreased energy consumption from maintaining the pool of IMP for salvage to AMP and then ATP, since de novo IMP synthesis requires burning seven ATPs. Similarly, beneficial effects have been seen in heart, skeletal muscle, or brain after treatment with allopurinol or febuxostat to inhibit xanthine oxidoreductase, which catalyzes hypoxanthine->xanthine and xanthine->urate reactions. Some disorders of those organs may reflect dysfunction in energy-consumption/production, and the observed beneficial effects related to reinforcement of ATP re-synthesis due to increased hypoxanthine levels in the blood and tissues. Recent clinical studies indicated that treatment with xanthine oxidoreductase inhibitors plus inosine had the strongest impact for increasing the pool of salvageable purines and leading to increased ATP levels in humans, thereby suggesting that this combination is more beneficial than a xanthine oxidoreductase inhibitor alone to treat disorders with ATP deficiency.